War and individual rights the foundations of just war theory - Draper, Kai (Oxford University Press, 2016)
Drawing from the insights of John Locke and other thinkers in the natural rights tradition, Draper reaches the conclusion that, despite the moral obstacles posed from respecting such rights, sometimes war is justified.